2020
DOI: 10.21511/ppm.18(1).2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the level of financial and economic security at machine-building enterprises: evidence from Ukraine

Abstract: Determining the level of financial and economic security of an enterprise allows assessing the real possibilities to confront internal and external challenges and defining the potential for future development. To develop proposals on assessing this level, the study uses data on machine-building enterprises of Zaporizhzhia region (Ukraine) and applies integral method, regression analysis and normalization. The expert evaluation method was used to form the system of key parameters. The experts were economists, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…On the basis of the continuous innovation of the registration system, the number of approval items will increase to a certain extent, however, in the current business administration work, there is no perfect interconnection mechanism between functional departments, which has greatly affected the efficiency of information sharing and restricted the improvement of certification efficiency. From the perspective of the regulatory model, although the industrial and commercial administration has built an online transaction supervision platform, the overall regulatory model is relatively backward due to technical factors, especially for some grass-roots industrial and commercial departments, this problem is particularly obvious, the existing hardware environment and technical conditions cannot meet the corresponding requirements, which restricts the improvement of regulatory efficiency [15].…”
Section: Working Mechanism To Be Improvedmentioning
confidence: 99%
“…On the basis of the continuous innovation of the registration system, the number of approval items will increase to a certain extent, however, in the current business administration work, there is no perfect interconnection mechanism between functional departments, which has greatly affected the efficiency of information sharing and restricted the improvement of certification efficiency. From the perspective of the regulatory model, although the industrial and commercial administration has built an online transaction supervision platform, the overall regulatory model is relatively backward due to technical factors, especially for some grass-roots industrial and commercial departments, this problem is particularly obvious, the existing hardware environment and technical conditions cannot meet the corresponding requirements, which restricts the improvement of regulatory efficiency [15].…”
Section: Working Mechanism To Be Improvedmentioning
confidence: 99%
“…Therefore, the researcher established how interest rate impact and performance of financial institutions. Ukraine, Cherep et al (2020) researched on Assessment of the level of financial and economic security at machine-building enterprises, estimated based on the values of the following generalized groups of indicators: financial sustainability, liquidity and solvency, business sentiment, profitability, investment attractiveness, and innovative development. The research demonstrated that the efficiency of the management system may alter the degree of financial and economic security for any size of organization.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Recommendations for analyzing and managing financial security boil down to 'the need to use a system of indices, indicators and methods'. At best, there is a list of indicators that exactly coincide with the economic analysis indicators used to assess an enterprise's financial condition (Cherep et al 2020;Turgaeva et al 2020). At worst, there are only unfounded 'recommendations' for managing or assessing a company's financial security.…”
Section: Introductionmentioning
confidence: 99%